Analisis Pengaruh Testimonial Dan Endorsement Terhadap Minat Beli Busana Muslimah: Indonesia - Lauren, Febi; safitri, junaidi (Asian Journal of Innovation and Entrepreneurship, 2022)
Cyber crime is a crime that utilizes technological developments, especially the internet. As a result, online fraud causes a lack of trust from potential consumers to online shops. This study aims to analyze how the influence of testimonials and endorsements on the interest in buying Muslim clothing, and which variables have the most influence between testimonials and endorsements. These testimonials and endorsements are one of the supporting factors to increase the trust of potential consumers tostores online due to the many reports offraud online that occur. This study uses quantitative methods, the data used are primary data by distributing questionnaires to 119 respondents in accordance with predetermined criteria. The non-probability sampling technique is the purposive sampling method according to the criteria. The data collection analysis technique is multiple linear regression analysis. The results of data processing concluded the results of the t test (pasrial), that the T variable was positive and significant to MB. And the estimated value of the E variable also shows a positive and significant impact on MB. The result of the f test (simultaneous) has a calculated F value of 42.111 with a significance level of 0.000. A significance value of 0.000 is smaller than an alpha of 0.05 indicating that the independent variables Testimonials (T) and Endorsements (E) simultaneously have a significant effect on the dependent variable, namely Purchase Interest (MB). The results of the coefficient of determination (R2) with a value of 0.411 or 41.4%. This shows that the influence of the independent variable on the dependent variable is 41.1% and the remaining 59.6% is explained by other variables that are not included in the regression model.